2001
DOI: 10.1111/j.1524-4725.2001.99315.x
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin in the Treatment of Keloids and Hypertrophic Scars by Multiple Needle Punctures

Abstract: Background. The treatment of keloids and hypertrophic scars has been difficult and a recent French study showed that bleomycin has been useful in the treatment of these lesions. Objective. To determine the effectiveness and safety of bleomycin in the treatment of hypertrophic scars and keloids when this drug is administered through multiple superficial punctures. Methods. We applied bleomycin to keloids and hypertrophic scars in 13 patients using a multiple-puncture method on the surface of the skin. All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 25 publications
1
45
1
3
Order By: Relevance
“…After administering three to five intralesional injections of bleomycin within a 1-month period, the authors observed complete regression in 69.4% of the keloids. Subsequent studies revealed similar results, with significant improvement in hypertrophic scar and keloid height and pliability as well as reduction in erythema, pruritus and pain (135,137,138). Occasionally, development of hyperpigmentation and dermal atrophy may occur with bleomycin treatment.…”
Section: Current Treatment Strategiessupporting
confidence: 55%
“…After administering three to five intralesional injections of bleomycin within a 1-month period, the authors observed complete regression in 69.4% of the keloids. Subsequent studies revealed similar results, with significant improvement in hypertrophic scar and keloid height and pliability as well as reduction in erythema, pruritus and pain (135,137,138). Occasionally, development of hyperpigmentation and dermal atrophy may occur with bleomycin treatment.…”
Section: Current Treatment Strategiessupporting
confidence: 55%
“…Finally, bleomycin can cause pulmonary, renal, and cutaneous fibrosis at high doses. Doses of bleomycin used for intralesional punctures have shown less than 5% systemic absorption [32]. Ifthese side effects can be minimized or eliminated, treatment with antineoplastic drugs may be feasible for fibroproliferative disorders that have many of the same characteristics of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Mögliche Nebenwirkungen sind Hautirritationen, Schmerzen während der Injektion, Ulzerationen und Purpura. Auch über intraläsionales Bleomycin existieren durchaus positi− ve Studienergebnisse [24,25]. Durch ein ¹Einpricken" der Sub− stanz, d. h. externes Auftragen und anschließende Punktion mit einer Nadel, findet eine geringere Resorption statt.…”
Section: Intraläsionale Zytostatikaunclassified